Pengembangan Sistem Pendidikan Hukum Pidana untuk Masyarakat - Ridwan Lubis, Muhammad; Nurita, Cut; Lubis, Diana; Novita, Rini; Armaini Ry, Agus (Bulletin of Community Engagement, 2024)
Questioning the existence of law that lives in society in reforming criminal law is an important challenge in developing a legal system that is in accordance with changing social dynamics. In this endeavor, it is important to consider two main perspectives: juridical and theoretical. From a legal theory perspective, the position of law as it exists in society in reforming criminal law can be seen as a reflection of the interaction between existing norms in society and norms produced by formal legal institutions. This legal theory emphasizes the importance of understanding how informal norms that exist in society, such as customs, values ??and traditions, can influence the development of criminal law. In this context, the law that lives in society is not something separate or independent, but is an integral part of the formation and renewal of criminal law. This research applies a normative juridical approach with a focus on descriptive analysis. The results of this research show that there is a contribution of law that lives in society in reforming criminal law, which has strong theoretical support. This shows that in developing or updating criminal law, it is important to consider not only the norms established by formal legal institutions, but also the social realities and values ??that live in society. In addition, justification for adopting these social rules in criminal law reform can be found not only in national law, but also in international law, which shows the relevance and importance of global norms in the local context. Keywords: Development Criminal Law Education System, Criminal Law Education System